2020
DOI: 10.1186/s40834-020-00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Spousal age difference and its effect on contraceptive use among sexually active couples in Ethiopia: evidence from the 2016 Ethiopia demographic and health survey

Abstract: Background Age difference among spouses can be considered as an indicator of the nature of the marital bond, and influences the couple’s fertility expectations. The age difference is one of the features of the traditional African marriage system. However, the likelihood that women use of contraceptives and spousal age differences is not well studied. Thus, this study was to examine the spousal age difference on contraceptive use. Objective This study was aimed to examine spousal age differences and its effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
10
1
Order By: Relevance
“…This might also be an indication of the little relevance of relative household wealth on reproductive health in communities where the rich among the poor are also poor because of the collective orientation they share. Though this specific finding contrasts with a glut of earlier studies in Nigeria and elsewhere that have established the increased use of modern contraceptives among the wealthier and least deprived groups ( 33 36 ), it, however, compares with a few other studies that have found higher contraceptive prevalence among women residing in resource-poor communities ( 37 , 38 ) indicating the importance of zeroing in on specific vulnerable groups to understand their specific needs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This might also be an indication of the little relevance of relative household wealth on reproductive health in communities where the rich among the poor are also poor because of the collective orientation they share. Though this specific finding contrasts with a glut of earlier studies in Nigeria and elsewhere that have established the increased use of modern contraceptives among the wealthier and least deprived groups ( 33 36 ), it, however, compares with a few other studies that have found higher contraceptive prevalence among women residing in resource-poor communities ( 37 , 38 ) indicating the importance of zeroing in on specific vulnerable groups to understand their specific needs.…”
Section: Discussioncontrasting
confidence: 99%
“…In the south, however, higher wealth status predicts lower use of contraceptives. This finding may be due to a likelihood of low levels of empowerment among young girls in Northern Nigeria, in which case, they are married to older partners and they do not usually possess the agency to participate, either solely or partially, in the decision to utilize modern contraceptives, irrespective of the relative level of wealth in their household ( 33 ). This might also be an indication of the little relevance of relative household wealth on reproductive health in communities where the rich among the poor are also poor because of the collective orientation they share.…”
Section: Discussionmentioning
confidence: 99%
“…Age difference with a partner was found to have a negative association with the use of contraceptives amongst female GBV survivors. Similar findings were obtained by researchers such as Ibisomi ( 2014) in Nigeria and Kitila (2020) in Ethiopia. In this study, a one year increase in age difference with partner decreased the odds of using contraceptives by 16 %.…”
Section: Determinants Of Contraceptive Usesupporting
confidence: 90%
“…A study done in Ethiopia by Kitila et al (2020) revealed that spousal age difference affects contraceptive use negatively. Women with spouses who were 10 years older were less likely to use contraceptives.…”
Section: Review Of Literaturementioning
confidence: 99%
“…“Couple age difference” was obtained by subtracting woman’s age from her husband’s age (age of husband − age of a woman) and further categorized as “negative” (age of a woman is greater than that of husband), “equal” (age of woman and husband is equal), “less than 10 years” (husband is less than 10 years older than women), and “equal or greater than 10 years” (husband’s age exceeds women’s age by 10 years and above). 46 …”
Section: Methodsmentioning
confidence: 99%